Contact skin temperature measurements and associated effects of obstructing local sweat evaporation during mild exercise-induced heat stress. (3rd July 2018) - MacRae, Braid A; Rossi, René M; Psikuta, Agnes; Spengler, Christina M; Annaheim, Simon
Abstract: Objective : Locally increasing evaporative resistance is one mechanism by which contact skin temperature ( T sk ) sensors and their attachments may disturb the temperature of the skin site being measured. We aimed to determine the extent to which an obstruction of evaporation affects local T sk during exercise-induced sweating and how this compares to the T sk measured using a conventional contact T sk sensor. Approach : Twelve adult males each completed one experimental session (~24 °C, ~46% relative humidity) involving seated rest and exercise (cycle ergometer). Air velocity was ~0.5 m · s −1 during rest and ~1 m · s −1 during exercise. T sk of the right posterolateral forearm was measured using fine-wire thermocouples (0.125 mm diameter; chosen for minimal sensor-related disturbance) under two concurrent experimental conditions: uncovered or directly covered by a moisture-impermeable matte-black aluminium foil (thickness 0.08 mm, area 15 mm  ×  22 mm). The adjacent T sk was also measured using an iButton attached with a nonwoven medical tape. Changes in next-to-skin absolute vapour pressure were used to estimate the onset of sweating. Main results : During exercise, covered thermocouple temperatures were consistently warmer than those uncovered. These differences were small before the onset of sweating (0.1 °C, p   =  0.16), but increased thereafter (0.6 and 1.0 °C by minutes 15 and 30 of exercise, respectively; p   ⩽  0.03). For change scores from baseline rest, the iButton-measured T sk was as much as 0.7 °C warmer than uncovered and −0.4 °C cooler than covered thermocouples during sweating, but differences were not statistically supported and with wide 95% limits of agreement (up to  ±3.1 °C). Significance : When delineated, a small obstruction of evaporation itself caused an overestimation of T sk during exercise although, while demonstrable, these effects were less clear in the context of using a conventional contact T sk sensor and attachment.